Identifying Research-Based Parameters for Developing Public Higher Education Outcomes-Based Funding Models - Knepp, Richard Nelson (My University, 2016)
The purpose and outcome of this study was to provide insight into clearly articulated parameters that might serve as a basis for the development of a generalizable outcomes-based funding model that any higher education system could use. Funding models were analyzed and telephone interviews were conducted from the ten states that were identified by the National Center for Higher Education Management Systems (NCHEMS.Org) as having fully implemented funding models for the 2010 - 2015 fiscal years. The analysis of the funding models and research participant responses from these ten states provided the parameters that might serve as a basis for the development of a generalizable outcomes-based funding model that any higher education system could use.
I INTRODUCTION 1 | Georgia as an Example 2 | Workforce Context 6 | Complete College America – Complete College Georgia Context 8 | Higher Education Funding Context 11 | Description of the Study 12 | Theoretical Framework 13 | Statement of the Problem 15 | Purpose of the Study 15 | Research Questions 15 | Outcomes of the Study 16 | Limitations 17 | Assumption 18 | Definition of Key Terms 18 | II REVIEW OF THE LITERATURE 21 | Introduction 21 | Follow the Money: How It Started 22 | Follow the Money: Who Gets It? 24 | Follow the Money: A New Idea 29 | Follow the Money: Does it Work? 34 | Theoretical Framework 37 | Summary 39 | III RESEARCH METHODOLOGY 41 | Introduction 41 | Statement of the Problem 42 | Purpose of the Study 42 | Research Questions 42 | Significance of the Study 43 | Research Design 43 | Population 44 | Data Collection Procedures 45 | Introduction E-mail and Survey Questionnaire Procedures 46 | Follow-up Telephone Interview Procedures 48 | Coding and Analysis of Data Procedures 51 | Instrumentation 53 | Data Gathering Instrumentation Validation 53 | Instrumentation Pilot Testing and Results 54 | Interview Pilot Testing and Results 55 | IV FINDINGS 60 | Introduction 60 | Funding Model Data Collection and Analysis Results 62 | Key Terms Review 64 | Funding Models: Preconceptions 64 | Findings from Analysis of Funding Models 68 | Funding Model Findings from Analysis of Interview Responses 80 | Funding Model Findings 85 | Unexpected Findings from Follow-up Telephone Interviews 86 | Chapter Summary 90 | V CONCLUSIONS 93 | Conclusions 94 | Discussion of Research Questions 98 | Recommendations for Further Research 105 | Final Significance 109 | REFERENCES 113 |
Keywords: Dissertations; Education, Higher; Georgia